Role of Arg1+ ILC2s and ILCregs in gestational diabetes progression - Zhangyun Gong; Haixing Yi; Jie Zhang; Wan Li; Hao Wang; Peipei Guo; Caihua Li; Anan Pan; Yunxia Cao; Zhimin Lu; Huanhuan Jiang (Scientific Reports)
Abstract Innate lymphoid cells (ILCs) are a newly discovered subset of immune cells that are responsible for regulation of the immune microenvironment. In particular, the ILC categories ILC2s and regulatory ILCs (ILCregs) are associated with immunosuppression and chronic inflammation. Chronic low-grade inflammation leads to insulin resistance, a major etiological factor in gestational diabetes mellitus (GDM). However, the influence of ILCs on GDM remains poorly understood. Therefore, this study aims to investigate the potential role of ILCs in the development and progression of GDM. This study included 19 patients diagnosed with GDM and 19 age- and body mass index-matched individuals in the control group. Flow cytometry was employed to assess the frequency and function of ILC subsets in peripheral blood (PB), cord blood (CB), and placental tissues. Additionally, ELISA was utilized to measure the levels of the cytokines TNF-α, IFN-γ, TGF-β, and IL-4/10/13/22 in the serum samples of patients. Compared to the control group with normal pregnancy, significantly elevated levels of ILC2s, Arg1+ILC2s, and ILCregs were detected in the PB, CB, and placental tissues of the GDM group. With regard to inflammation-related cytokines, the levels of IL-13/22 in PB serum were significantly elevated, while the TGF-β levels were significantly reduced in the GDM group compared to the control group (CG). Further, in the CB serum samples, IL-13 levels were elevated in the GDM group. Additionally, a negative correlation was observed between the number of ILC3s and the number of ILCregs present in umbilical cord blood, while the IL-13 level in peripheral blood was negatively correlated with the number of ILC3s. The present findings indicate that chronic low-grade inflammation mediated by Arg-1+ILC2s and ILCregs is closely associated with the pathogenesis of GDM.